Pendekatan Pemberdayaan Dalam Penanganan Permukiman Squatter: Sebuah Evaluasi Empiris - Hudalah, Delik (Center for Research and Community Services ITB, 2005)
Empowerment approaches in order to alleviate poverty and promote sustainable development are not new and still need further research on the concept, planning, and implementation. Involving the World Bank and other non -government institutions, the Government of Indonesia since 2003 develop ed those approaches which are more integrated and participative through Squatter Settlemen its Pilot Assistance Project (PPM-Squatter). This paper critiques and corrects the domination of those non -government institutions in financing and assisting the project/program. This paper also shows factors that determine the performance of empowerment ap proaches in squatter settlements assistance, which are (1) interpretation of concept of the program and typology of squatter, (2) political absorption by government institutions in all level, and (3) facilitation, monitoring and evaluation.Keywords: empowerment approach, squatter settlement assistance, empirical evaluation